2016
DOI: 10.1128/jb.00141-16
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Sulfide Assimilation in Methanosarcina acetivorans Is Mediated by the MA1715 Protein

Abstract: Conserved genes essential to sulfur assimilation and trafficking in aerobic organisms are missing in many methanogens, most of which inhabit highly sulfidic, anaerobic environmental niches. This suggests that methanogens possess distinct pathways for the synthesis of key metabolites and intermediates, including cysteine, homocysteine, and protein persulfide groups. Prior work identified a novel tRNA-dependent two-step pathway for cysteine biosynthesis and a new metabolic transformation by which sulfur is inser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 27 publications
(46 reference statements)
6
18
0
Order By: Relevance
“…Of the 11 genuine gaps, we identified genes to fill nine of them; these novel enzymes explain the biosynthesis of four different amino acids by bacteria from six different genera. And we found that homocysteine synthesis in Desulfovibrio vulgaris Miyazaki F required DUF39, NIL/ferredoxin, and COG2122 proteins, as expected from studies of this pathway in other organisms (Rauch et al 2014;Rauch and Perona 2016;Kuehl et al 2014) . Our genetic data imply that, in contrast to all other known pathways, homoserine is not an intermediate in homocysteine synthesis in D. vulgaris.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…Of the 11 genuine gaps, we identified genes to fill nine of them; these novel enzymes explain the biosynthesis of four different amino acids by bacteria from six different genera. And we found that homocysteine synthesis in Desulfovibrio vulgaris Miyazaki F required DUF39, NIL/ferredoxin, and COG2122 proteins, as expected from studies of this pathway in other organisms (Rauch et al 2014;Rauch and Perona 2016;Kuehl et al 2014) . Our genetic data imply that, in contrast to all other known pathways, homoserine is not an intermediate in homocysteine synthesis in D. vulgaris.…”
Section: Introductionsupporting
confidence: 82%
“…This strongly suggests that the COG2122 protein is also required for homocysteine formation. In contrast, (Rauch and Perona 2016) found that the orthologous protein from Methanosarcina acetivorans ( MA1715) was important for growth in defined media at low sulfide concentrations, but that mutants could be rescued by either higher sulfide concentrations or by added cysteine or homocysteine. They proposed that COG2122 aids in the formation of an unknown intermediate in sulfide assimilation for both methionine and cysteine.…”
Section: Figure 3: Synthesis Of Methionine and Threonine In Desulfovimentioning
confidence: 90%
See 1 more Smart Citation
“…Hcy has also been shown to be an intermediate in Met and Cys metabolism in Archaea methanogens [43]. Because Hcy is a non-coded amino acid, living organisms must have evolved the ability to prevent its access to the Genetic Code.…”
Section: Homocysteine (Hcy) Is Edited By Class I and Class Ii Aminmentioning
confidence: 99%
“…The K M of Na 2 S is ~1 mM, close to the estimated intracellular concentrations of free sulfide in methanococci (~1–3 mM) [47]; this suggests that sulfide is a physiologically relevant sulfur donor. Furthermore, free l -cysteine is not a sulfur donor for the biosynthesis of Fe–S cluster [64] and tRNA thionucleosides [65] in methanogens; this suggests that a cysteine desulfurase is not required as a central sulfur donor for the biosynthesis of sulfur containing compounds. Notably, the methanogenic archaeal ThiI homologs have three conserved Cys residues (two from a CXXC motif) in the putative catalytic domain [46,47].…”
Section: Fe–s Cluster-dependent and Independent Trna Thiolation Prmentioning
confidence: 99%